Evidence of flow and low genetic structure between populations of the Gulf of Mexico and the Mexican Pacific of white mullet, Mugil curema (Pisces) inferred from single nucleotide polymorphisms - Ávila-Herrera, Concepción Lizette; Guevara-Chumacero, Luis Manuel; Velázquez- Aragón, José Antonio; Ibáñez, Ana Laura (Fisheries research, 2022)
Population genomics methodologies offer new tools for fine structure identification and contemporary connectivity, providing valuable information for the conservation and management of fish populations. NextRAD sequencing was used for obtaining single nucleotide polymorphisms (SNPs) throughout the Mugil curema genome, a species of fish of great ecological and commercial importance, with a wide genetic dissimilarity between its populations throughout its distribution. The population structure, connectivity, and genomic diversity of 95 individuals from three locations in the Gulf of Mexico (GoM) and six in the Mexican Pacific (MP) were evaluated with a set of 14, 172 SNPs. The spatial analyses identified three genetic groups with incipient divergence (FST= 0.1–0.513), low nucleotide diversity (π = 0.019–0.200), and moderate gene flow among populations (2.4–12.8 %). The first group included two localities of the GoM (Madre and Alvarado lagoons) connected with two of the MP (Huave System (HU) and Puerto Escondido (PE)), which presented a moderate exchange of genotypes of 10.5–11.1 % between both slopes, which could be due to the connection between sub-basins or tributaries of the Gulf of Tehuantepec region; the second connected the six localities of the MP; and the third only to individuals from Celestun (CE), a population that could be under a recent divergence process, due to the accumulation of their ecological, environmental and genetic differences. The results reflect a low contemporaneous population genomic structure and connectivity of Mugil curema in the GoM and MP, in addition, they do not support the mitochondrial hypotheses of the cryptic species Mugil curema “T2″ from the Atlantic and Mugil sp. "O" of the Pacific. •NextRAD sequencing was used to evaluate the connectivity of white mullets.•Population connectivity between the Gulf of Mexico and the Mexican Pacific.•The results identified three genetic groups with incipient divergence.•Populations of with mullet under a recent divergence process.